Controlling Defect and Dopant Concentrations in Graphene by Remote Plasma Treatments - MC MANUS, JOHN BRENDAN; Hennessy, Alison; Conor P., Cullen; Hallam, Toby; McEvoy, Niall; Georg S., Duesberg (My University, 2017)
This report details the controllable doping of graphene through post‐growth plasma treatments. Defects are controllably introduced into the lattice using argon plasma, following this sample are exposed to ammonia/hydrogen plasma. During this nitrogen atoms get incorporated causing partial restoration of the graphene lattice. The damage levels are characterised by Raman and X‐ray photoelectron spectroscopies. The incorporation of nitrogen into the graphene lattice provides significant n‐doping. This is confirmed by the fabrication of graphene field‐effect transistors which show clear n‐type behaviour and mobilities not significantly less than those of pristine graphene. Thus this work demonstrates the viability of plasma treatments to reliably dope graphene.
PUBLISHED
Keywords: Graphene; Plasma treatment; Nitrogen doping; Graphene transistor; Chemical vapor depositions (CVD); Nanoscience & Materials; CHEMICAL VAPOR-DEPOSITION; DOPING; Graphene; NITROGEN; PLASMA TREATMENT